2006
DOI: 10.1186/1465-9921-7-33
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-signaling in airway smooth muscle cells is altered in T-bet knock-out mice

Abstract: Background: Airway smooth muscle cells (ASMC) play a key role in bronchial hyperresponsiveness (BHR). A major component of the signaling cascade leading to ASMC contraction is calcium. So far, agonist-induced Ca 2+ -signaling in asthma has been studied by comparing innate properties of inbred rat or mouse strains, or by using selected mediators known to be involved in asthma. T-bet knock-out (KO) mice show key features of allergic asthma such as a shift towards T H 2-lymphocytes and display a broad spectrum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
(47 reference statements)
2
23
0
Order By: Relevance
“…On the basis of our previous results, we suggest that a heightened [Ca 2ϩ ] i mobilization through the CD38/cADPR pathway in ASM cells upon agonist stimulation contributes to the increased ASM contraction, leading to excessive airway narrowing and AHR in vivo. This suggestion is also supported by other studies showing that enhanced calcium signaling in ASM cells is associated with enhanced ASM contractility and AHR in vivo (3,36). This is anticipated since Ca 2ϩ is an important signaling molecule regulating ASM contraction and bronchomotor tone.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…On the basis of our previous results, we suggest that a heightened [Ca 2ϩ ] i mobilization through the CD38/cADPR pathway in ASM cells upon agonist stimulation contributes to the increased ASM contraction, leading to excessive airway narrowing and AHR in vivo. This suggestion is also supported by other studies showing that enhanced calcium signaling in ASM cells is associated with enhanced ASM contractility and AHR in vivo (3,36). This is anticipated since Ca 2ϩ is an important signaling molecule regulating ASM contraction and bronchomotor tone.…”
Section: Discussionsupporting
confidence: 74%
“…We have also shown that CD38KO airway myocytes have reduced [Ca 2ϩ ] i responses to contractile agonists and that methacholine-induced increases in airway resistance are lower in CD38KO mice compared with wild-type (WT) controls (8). These studies demonstrated that the CD38/cADPR signaling has an important role in [Ca 2ϩ ] i homeostasis in ASM cells with clear implications to normal airway function.Changes in [Ca 2ϩ ] i homeostasis have been proposed to be an important mechanism underlying airway hyperresponsiveness (AHR), a prominent feature of the asthmatic phenotype (3,15,36). Previous studies from our laboratory and from others using human ASM cells have implicated the CD38/cADPR signaling in [Ca 2ϩ ] i hyperresponsiveness to contractile agonists with possible relevance to inflammatory airway diseases (7,18,19,37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lung slices were prepared as described previously (Bergner and Sanderson, 2002;Bergner et al, 2006). In brief, C57BL/6J mice (15-18 weeks old) were euthanized by CO 2 followed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…Other functions of CRT include calcium homeostasis and quality control of protein folding. In a mouse model, it was shown that increased contractility in lung slices correlated with increased calcium in the sarcoplasmic reticulum (SR) [18]. CRT in the SR serves as a calcium chelator and may prevent release of calcium from the SR into the cytoplasm and, therefore, contraction.…”
mentioning
confidence: 99%